Penerapan Media Scribe Materi Hak Dan Kewajiban Warga Negara Untuk Meningkatkan Motivasi Siswa Kelas IV Sekolah Dasar - Prameswari, Noviardani Kartika (Universitas Nusantara PGRI Kediri, 2019)
This research is motivated because there is a low motivation to learn grade IV students due to the lack of use of learning media used for teaching and learning by the teacher. With the application of Scribd learning media, students are more motivated to learn in class. The research method used was Classroom Action Research (CAR) where in this study there were two cycles consisting of planning, implementing, observing, and reflecting in each cycle. While the subjects in this study were grade IV students, amounting to 20 students. Then the data collection techniques used in this study are by using observası and questionnaires. On the results of observations of teacher activity obtained from the results of the first cycle with a score of 41 with a percentage of 64.0% categorized as good and the second cycle the score became 61 with a percentage of 95.3% categorized as very good so thus the observation of teacher activity is said to increase, on the results of observations of student activities the first cycle with a score of 35 with a percentage of 58.3% was categorized as sufficient, in the second cycle the score became 57 with a percentage of 95.0% with a very good category. Therefore the observation of student activity is said to increase using the media scribe Percentage of students who have learning motivation categories good and very good in the pre-study reached 40.0% categorized as less, the percentage in the first cycle to 70.0% which has a good category so that there was an increase from pre-study to the first cycle of 30.0%, whereas in the second cycle increased to 85, 0% has a very good category, the increase from cycle I to cycle II is 15.0%. Thus it can be concluded that the application of scribe media can increase student motivation in the material Rights and Obligations of Indonesian citizens class IV at SDN II Pasinan.